The Effect of Work Motivation on Organizational Citizenship Behavior Through Job Satisfaction as a Mediation Variable - Saputra, Muhamad Ajye; Soetjipto, Budi Eko; Winarno, Agung (Universitas KH. Abdul Chalim Mojokerto, 2026)
Organizational Citizenship Behavior (OCB) refers to voluntary behavior exhibited by employees that goes beyond their formal job descriptions and contributes positively to the overall effectiveness of the organization. This study aims to analyze the influence of Servant Leadership and Work Motivation on Organizational Citizenship Behavior (OCB) with Job Satisfaction as a mediating variable among employees of PT Karya Usaha Baru. The research employed an explanatory research design, with a population consisting of 1,500 non-managerial employees. A total of 306 respondents were selected as samples, and data were collected using online questionnaires distributed via Google Forms. The data were analyzed using the path analysis method. The results of this study indicate that: (1) Servant Leadership has a positive and significant direct effect on Organizational Citizenship Behavior, meaning that a service-oriented leadership style enhances employees’ organizational citizenship behavior. (2) Work Motivation has a positive and significant direct effect on Organizational Citizenship Behavior, indicating that employees’ internal drive contributes to the improvement of OCB. (3) Servant Leadership has a positive and significant effect on Job Satisfaction, implying that servant leaders can increase employee job satisfaction. (4) Work Motivation has a positive and significant effect on Job Satisfaction, suggesting that higher motivation is associated with greater job satisfaction. (5) Job Satisfaction has a positive and significant effect on Organizational Citizenship Behavior, meaning that satisfied employees are more likely to display OCB. (6) Job Satisfaction partially and significantly mediates the indirect effect of Servant Leadership on Organizational Citizenship Behavior. (7) Job Satisfaction also partially and significantly mediates the indirect effect of Work Motivation on Organizational Citizenship Behavior among employees of PT Karya Usaha Baru.